2016
DOI: 10.1007/s11250-016-1183-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of post-mating hCG or progesterone administration on reproductive performance of Afshari × Booroola-Merino crossbred ewes

Abstract: To investigate the efficiency of hCG/CIDR after breeding to increase the reproductive performance, 35 synchronized ewes were mated with fertile rams and were assigned to three treatment groups. Ewes in hCG group (n = 12) received 400 IU hCG on day 11 post-mating, and ewes in CIDR group (n = 11) received CIDR from day 7 until day 19 post-mating. Ewes in the control group (n = 12) did not receive any treatment. Blood samples were collected on days 7, 12, 17, and 22 post-mating. Plasma P concentrations were highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Therefore, it may be usefull that gonadotropic hormone injections are applied in order to support luteal structure and to increase progesterone levels in this critical term (Khan et al 2006). Rostami et al (2017) pointed out that GnRH injections applied between 7 and 19 days following mating may be important, although 12th day of gestation is critical for preventing luteolysis, because insufficient and abnormal luteal function in this period detrimentally affect embryonic development and cause embryonic loss (Spencer et al 2004). A study made by Beck et al (1996) reported that GnRH injection on day 12 post-mating improves reproductive outcome; these applications are essential for successful implantation and progression of gestation, supports follicular and luteal function with increased LH pulses, survival and quality of developing embryos can be improved during pre-implantation period (Khan et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it may be usefull that gonadotropic hormone injections are applied in order to support luteal structure and to increase progesterone levels in this critical term (Khan et al 2006). Rostami et al (2017) pointed out that GnRH injections applied between 7 and 19 days following mating may be important, although 12th day of gestation is critical for preventing luteolysis, because insufficient and abnormal luteal function in this period detrimentally affect embryonic development and cause embryonic loss (Spencer et al 2004). A study made by Beck et al (1996) reported that GnRH injection on day 12 post-mating improves reproductive outcome; these applications are essential for successful implantation and progression of gestation, supports follicular and luteal function with increased LH pulses, survival and quality of developing embryos can be improved during pre-implantation period (Khan et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Gonadotropin releasing hormone (GnRH) or human chorionic gonadotropin (hCG) injections are applied concurrently with mating or just after in order to prevent embryonic and foetal loss or to increase reproductive performance in ewes (Beck et al 1994;Nephew et al 1994;Cam and Kuran 2004;Khan et al 2007;Ataman et al, 2013;Ahmadi and Mirzaei 2016;Rostami et al 2017). Embryonic loss generally results from inadequate early luteal function and insufficient progesterone levels during pre-implantation period (Spencer et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher plasma P 4 concentrations was reported in post‐mating hCG‐treated groups in Afshari × Booroola‐Merino crossbred ewes by Rostami et al. (2017). Injection of GnRH on the day of oestrus or at the time of mating and 7 or 9 days later increased serum P4 concentration.…”
Section: Introductionmentioning
confidence: 71%
“…The use of gonadotropin releasing hormone (GnRH) or the male effect in PGF2α-based protocols was reported previously (Mirzaei et al, 2017;Olivera-Muzante, Gil, Fierro, Menchaca, & Rubianes, 2011). Human chorionic gonadotropin (hCG) and GnRH administrations on the day of mating or post-mating were applied for improving the reproductive performance (conception, lambing, twining rate and litter size) of different breed (Akkaraman, fat tailed, Afshari × Booroola-Merino crossbred, Anatolian Merino) ewes (Ahmadi & Mirzaei, 2016;Ataman, Aköz, Sarıbay, Erdem, & Bucak, 2013;Dursun, 2019;Rostami, Hajizadeh, Shahir, & Aliyari, 2017). A higher plasma P 4 concentrations was reported in post-mating hCG-treated groups in Afshari × Booroola-Merino crossbred ewes by Rostami et al (2017).…”
Section: Introductionmentioning
confidence: 99%